Phosphorylation of RIPK1 serine 25 mediates IKK dependent control of extrinsic cell death in T cells - Blanchett, Sam; Dondelinger, Yves; Barbarulo, Alessandro; Bertrand, Mathieu J. M.; Seddon, Benedict (Frontiers in Immunology, 2022)
The Inhibitor of Kappa B Kinase (IKK) complex is a critical regulator of NF-κB activation. More recently, IKK has also been shown to repress RIPK1 dependent extrinsic cell death pathways by directly phosphorylating RIPK1 at serine 25. In T cells, IKK expression is essential for normal development in the thymus, by promoting survival of thymocytes independently of NF-κB activation. RIPK1 undergoes extensive phosphorylation following TNF stimulation in T cells, though which targets are required to repress RIPK1 has not been defined. Here, we show that TNF induced phosphorylation of RIPK1 at S25 is IKK dependent. We test the relevance of this phosphorylation event in T cells using mice with a RIPK1S25D phosphomimetic point mutation in endogenous RIPK1. We find that this mutation protects T cells from TNF induced cell death when IKK activity is inhibited in vitro, and can rescue development of IKK deficient thymocytes in vivo to a degree comparable with kinase dead RIPK1D138N. Together, these data show that phosphorylation of RIPK1Ser25 by IKK represents a key regulatory event promoting survival of T cells by IKK.